Organhaftung und Beweislast - Danninger, Nadja (Bucerius Law School Hamburg, 2020)
Die Organhaftung zeigt eine beweisrechtliche Besonderheit: Nicht die Gesellschaft muss die Pflichtverletzung beweisen, sondern das Organmitglied muss sich nach § 93 Abs. 2 Satz 2 AktG (analog) entlasten. Die Beweislastumkehr wirft in der Praxis eine Reihe von Problemen auf, und auch ihre theoretische Fundierung harrte bislang einer abschließenden Klärung. Nadja Danninger beleuchtet das Thema nach einer beweisrechtlichen Einführung aus fünf Blickwinkeln: Rechtsgeschichte, Rechtsdogmatik, Rechtspraxis, Rechtsvergleichung und Rechtspolitik. Die Verfasserin legt die römisch-rechtlichen Wurzeln ebenso frei wie die höchst unterschiedliche Behandlung der Beweislastfrage in 15 untersuchten Rechtsordnungen. Neben der Analyse der Theorie untersucht sie ausgewählte praktische Konstellationen und zeigt damit auf, wie der beweisrechtliche Balanceakt in Theorie und Praxis gelingen kann.

Letztwillige Schiedsverfügungen : Geltungsgrund und Geltungsgrenzen - Gleim, Jakob (Mohr Siebeck, 2020)
Nach §1066 ZPO gelten die Vorschriften über vertraglich vereinbarte Schiedsgerichte entsprechend für "Schiedsgerichte, die in gesetzlich statthafter Weise durch letztwillige [...] Verfügungen angeordnet werden". Während solche letztwilligen Schiedsverfügungen im 20.Jahrhundert sehr selten waren, beschäftigen sie heute die deutschen Gerichte mit gewisser Regelmäßigkeit. Mit Zunahme der praktischen Relevanz rücken auch die dogmatischen Grundlagen letztwilliger Schiedsverfügungen in den Fokus: Warum darf der Erblasser nicht nur materielle, sondern auch prozessuale Verfügungen von Todes wegen treffen? Wie weit reicht die Zuständigkeit des letztwillig eingesetzten Schiedsgerichts? Und welches Recht ist anzuwenden, wenn der Erbfall grenzüberschreitende Bezüge aufweist? Jakob Gleim beantwortet diese Fragen und bezieht dabei im Rahmen eines Rechtsvergleichs auch das US-amerikanische Recht ein. Fürdie vorliegende Dissertation wurde Jakob Gleim mit der2020 der Max-Planck-Gesellschaft ausgezeichnet. Is it possible for the testator to mandate unilaterally that all disputes concerning the estate are to be arbitrated instead of litigated? While such a testamentary arbitration clause is an expression of the decedent’s freedom of disposition, it contradicts the beneficiaries’ right of access to a public court. In his dissertation, Jakob Gleim examines the tension between the decedent’s freedom of disposition and the rights of the beneficiaries, balancing these two positions against one another and thereby identifying the reasons and the limitations of the validity of testamentary arbitration clauses. While such clauses were rather rare in the 20th century, German courts have to deal with them more regularly nowadays. In his dissertation, Gleim explores the practical significance of testamentary arbitration clauses as well as their advantages and disadvantages. The author also addresses the questions of how far the jurisdiction of the arbitral tribunal extends and which law is to be applied in cross-border cases. The inquiry also includes insights gained from a comparative analysis of US-American law.
Bucerius Law School Hamburg ISSN 2568-7441
Keywords: Arbitaje; Arbitrage; Arbitragem; Arbitration; Arbitration clause; Bankruptcy; Clause d'arbitrage; Insolvency; Mediation; Negotiation

Zukunftsfähiger internationaler Rechtsrahmen für Investitionen in Afrika - Gramlich, Ludwig (Recht in Afrika, 2020)
The future of sustainable development in Africa and for its growing population will depend on investments which might come mostly from abroad attracted by a favourable investment climate (or ecosystem). It is rather doubtful that the actual ('old') international legal framework for investment-related and investment-specific measures which does hardly create an adequate balance between the interests of all important public as well as private stakeholders would meet the requirement of today and tomorrow. But any alterations or improvements must start from the present state of things. So, this study looks at the different levels and various instruments dealing with traditional standards of investment and investor protection, e.g. BITs und TIPs, and at the activities of global, regional and sub-regional organizations (in particular EU and OHADA). Moreover, new developments at global and regional levels are discussed including trends showing a somewhat specific African approach to investment issues ('Africanization'). Finally, a very important topic, i.e. the relation between investment protection and human rights (of investors and of other people negatively affected by relevant activities), is described and assessed in more detail. A second part of the analysis will turn to elaborating on dispute settlement and enforcement issues since till today, there seems to be a sharp distinction between Investor-State- Dispute Settlement (ISDS) by way of mediation, conciliation and arbitration on the one hand and judicial redress by national courts (of home, host or third States) on the other.

Vereinheitlichung des Wirtschaftsrechts in Afrika durch die OHADA - Monsenepwo Mwakwaye, Justin (Rabels Zeitschrift für ausländisches und internationales Privatrecht, 2020)